Pengabdian Masyarakat Pada UMKM Pengunaan Facebook Sebagai Media Internet Marketing - Cantika, Yella; Anzori, Anzori; Harwini, Dewi; Fitriano, Yun; Subhi, Ramadan (LPPM Universitas Dehasen Bengkulu, 2024)
This community service aims to inscrease the competitiveeness and market reach of the Al muslim Clothing Shop MSMEs located in the central pasar through the implementation of Facebook marketplace technology.In the current digital era,utilizing online platforms is very important to expand markets and increase sales,This shervice actifity involves several stages,namely:training in usang the facebook marketplace ,technical assistence in creatin and managing business accounts,as well as effective digital marketing strategis.The methods used in this program include interactive training sessions,one-on-one mentoring,and regular evaluation of developments in marketplace use.The results of this activity show in the knowledge in using digital technology for their business.